Analisis Kerjasama Lanjutan Industri Pertahanan Indonesia 2012-2021 PKR SIGMA 10514 - Rahmawati, Lola; Widyarsa, Mohammad Riza (Indonesian Perspective, 2023)
PT PAL Indonesia's collaboration with Damen Schelde Naval Shipbuilding (DSNS) Netherlands in procuring the PKR SIGMA 10514 ship was successful. The two ships have arrived and are operating to date to fulfill Indonesia's national interests. However, the impact of cooperation is Indonesia's lack of prepared capacity to absorb technology and knowledge. The increasing intensity of threats every year encourages increasing independence and defense equipment. Indonesia collaborates with other countries, instead of continuing cooperation with the Dutch DSNS to optimize the transfer of technology. The focus of this research is to analyze the continuation of PT PAL's collaboration with DSNS Netherlands. The theoretical framework of this research uses Donald Nuechterlein's concept of national interests, which focuses on defense interests and economic interests in implementing PKR SIGMA 10514 as research analysis variables. The research results show that Indonesia is pursuing quality and quantity to improve its maritime defense posture from increasingly complex threats and needs a ship with equivalent specifications and weapons to replace the KRI Ahmad Yani. The research discusses it thoroughly and provides several views supported by primary and secondary data to strengthen the results of the discussion. Kerjasama PT PAL Indonesia dengan Damen Schelde Naval Shipbuilding (DSNS) Belanda dalam pengadaan kapal PKR SIGMA 10514 berhasil. Dua kapal tersebut telah tiba dan beroperasi sampai saat ini untuk memenuhi kepentingan nasional Indonesia. Namun, dampak dari kerjasama yaitu kurangnya kesiapan kapasitas Indonesia menyerap teknologi dan ilmu. Intensitas ancaman yang semakin meningkat tiap tahunnya mendorong untuk meningkatkan kemandirian dan alutsista. Indonesia menjalin kerjasama dengan negara lain, bukan melanjutkan kerjasama dengan DSNS Belanda untuk mengoptimalkan transfer of technology. Fokus penelitian ini adalah menganalisis lanjutan kerjasama PT PAL dengan DSNS Belanda. Kerangka teoritis penelitian ini dengan konsep kepentingan nasional pemikiran Donald Nuechterlein, yang terfokus dengan kepentingan pertahanan dan kepentingan ekonomi implementasi PKR SIGMA 10514 sebagai variabel analisis penelitian. Hasil penelitian menunjukkan Indonesia mengejar kualitas dan kuantitas untuk meningkatkan postur pertahanan maritim dari ancaman yang semakin kompleks serta perlu kapal yang setara spesifikasi dan senjatanya untuk menggantikan KRI Ahmad Yani. Penelitian membahas secara menyeluruh dan memberikan beberapa pandangan yang didukung data primer dan sekunder  untuk memperkuat hasil pembahasan.